Diminutives in Croatian: The Interface of Morphology, Semantics and Pragmatics - Žic Fuchs, Milena; Kraljević, Marija (2011)
Traditionally, diminutives in Slavic languages have been primarily studied from the point of view of diminutive formation, often with special emphasis on the morphophonemic aspects, such as consonant mutation. In grammars of Slavic languages, diminutives are often dealt with in terms of listing different suffixes used in diminutive formation, but without analyzing the internal organization of the category, that is, without showing the correlation between its morphology and semantics. For Croatian, Babić (2002³) in his Word Formation in the Croatian Literary Language analyzes 37 suffixes used in diminutive formation, including their morphophonemic characteristics. This in itself is an indication of a high degree of complexity of diminutive derivatives. The focus of this paper will be noun diminutive formation in Croatian, which apart from covering 37 suffixes also implies their selective distribution over three genders: masculine, feminine and neuter. In more recent approaches to diminutives in different languages, more and more attention has been paid to the semantic and pragmatic dimension (Wierzbicka 1980, 1984 ; Dressler and Merlini Barbaresi 1994). Jurafski (1996) views the diminutive category as a radial category, a structured polysemy that models the senses of the diminutive through metaphorical and inferential relations, while Taylor (1989:147) also sees diminutive morphemes as polysemous, claiming the meanings are linked through metaphor or metonymy. The shift to semantic and pragmatic considerations without a doubt sheds more light on the diminutive category. However, when one views a language such as Croatian, with its rich inventory of diminutive suffixes, the question arises whether the underlying semantic/pragmatic basis ties in not only with the complexity of interrelated senses, but also with the complexity of the diminutive derivations. Based on a representative corpus of noun diminutives, extracted from the Croatian National Corpus (over 2000 sentences), we will show how diminutives form a polysemous category in Croatian. This analysis will also show how the different suffixes cut across the meanings of the Croatian diminutives and, what is more, show consistent correlations within the category. In this way a coherent system becomes manifest and reduces what seems to be unfathomable complexity into a relatively well-ordered network. Interpreting diminutive morphology on the basis of semantics and pragmatics also provides insights into why some diminutive derivations are productive, and others are not.
Projekt MZOS
ENG